PDF Fiber Laser Effect on Bond Strength of Titanium implant abutment to Resin Cement - Abdulrazzaq, Ruba Husam; Basima Mohammed Ali Hussein (Iraqi Journal of Laser, 2022)
Aim: surface modification of titanium using fiber laser 1064 nm to enhance the bond strength to resin cement. Material and Methods: thirty titanium discs of 0.6 cm x 0.3 cm (diameter and thickness respectively) were categorized after preparation into three groups (n=10) as follows: control group with no surface treatment and two test groups were treated with fiber laser after estimation the appropriate parameters in the pilot study which are 81 ns pulse duration, 30,000 Hz frequency, 50 µm spot size and 10,000 mm/s scanning speed and different average power values (10 W and 20 W) depending on the tested group. Titanium discs surface characterization was performed by scanning electron microscope (SEM), and surface roughness tester. Following these tests, resin cement application to titanium discs was performed. Shear bond strength (SBS) values were determined by universal testing machine. ANOVA and Tukey HSD tests were used for analyzing of data (α = 0.05).Results: Higher average surface roughness (Ra) value was observed in (10 W) group followed by (20 W) group and the lowest surface roughness value was in the control group, additionally lowest SBS value was obtained from the control group and the highest SBS value was obtained from (20 W) group followed by (10 W) group. Conclusion: bond strength between titanium and resin cement can be significantly enhanced by using fiber laser as a surface treatment. Average power of fiber laser is essential parameter in enhancing the roughness of titanium surface and bonding to resin cement.